Biospheric processes forecasting by the means of synergetics - Azarov, S. I.; Zadunaj, O. S (КНУБА, 2018)
Among the most pressing problems of modernity stands out the problem of determining the causes and limits of sustainability of complex ecosystems, consisting of a huge number of components. Such systems include organisms and the biosphere with its ecosystems. Under the conditions of a global ecological crisis, the survival of humanity depends on our ability to understand and predict the behavior of ecosystems and the biosphere itself. Such forecast is a specific kind of perception, which, first, studies not what is happening, but what will be happening. The main purpose of the forecast is assessment of predicted environmental reaction to the direct or indirect human influence, as well as addressing the challenges of the future sustainable use of natural resources. We have developed methodical approaches to the biospheric processes evaluation with the help of synergestic approach are developed.
Прогнозування біосферних процесів за допомогою синергетики
Keywords: synergetics; biosphere; forecast; modeling; chaos; population; синергетика; біосфера; прогноз; моделювання; хаос; популяція; 504.75.05